1993
DOI: 10.1007/bf00196606
|View full text |Cite
|
Sign up to set email alerts
|

Iron uptake by leaf mesophyll cells: The role of the plasma membrane-bound ferric-chelate reductase

Abstract: Abstract. The uptake of 59Fe from FeC13, ferric (Fe 3+) citrate (FeCitr) and Fe3+-EDTA (FeEDTA) was studied in leaf mesophyll of Vigna unguiculata (L.) Walp. Uptake rates decreased in the order FeC13 > FeCitr>> FeEDTA, and uptake depended on an obligatory reduction step of Fe 3+ to Fe 2+, after which the ion could be taken up independently of the chelator, citrate. Uptake was strongly increased by photosynthetically active light (2 > 630 nm), and kinetic analysis revealed saturation kinetics with a K m (FeC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 23 publications
(17 reference statements)
1
81
0
3
Order By: Relevance
“…While FRO2 was not expressed in leaves, FRO3 was increased under iron defi- ciency both in the roots and in the leaves. The increase in leaf-localized FRO3 shows that reduction of ferric iron to ferrous is also a component of metal transport in the leaves (Table IIA) (34). Iron deficiency also led to decreased expression of ferritin genes in roots (AtFer1) and leaves (AtFer1 and AtFer4) (Table IIC).…”
Section: Up-regulation Of Iron Reductases and Irt2 And Down-regulatiomentioning
confidence: 94%
“…While FRO2 was not expressed in leaves, FRO3 was increased under iron defi- ciency both in the roots and in the leaves. The increase in leaf-localized FRO3 shows that reduction of ferric iron to ferrous is also a component of metal transport in the leaves (Table IIA) (34). Iron deficiency also led to decreased expression of ferritin genes in roots (AtFer1) and leaves (AtFer1 and AtFer4) (Table IIC).…”
Section: Up-regulation Of Iron Reductases and Irt2 And Down-regulatiomentioning
confidence: 94%
“…While the molecular mechanisms involved in iron transport into leaf cells remain unclear (Hell and Stephan, 2003). It has been reported that ferric chelate reductase activity is detectable in leaves of sunflower (Guardia and Alcantara, 1996) and Vigna unguiculata (Bruggemann et al, 1993). A recent study examined the fractionation of stable iron isotopes taken up from the soil in various aerial portions of bean, pea, soybean, maize, oat, wheat etc (Guelke and Von Blanckenburg, 2007).…”
Section: Grown On Iron Rich Wasteland Soilmentioning
confidence: 99%
“…Uptake of Fe(II1) by leaf mesophyll appears to depend on a reduction step via a PMbound Fe(lI1) chelate reductase, which most likely releases Fe(I1) from Fe(II1) citrate (Briiggemann et al, 1993). There is also some evidence that Fe(II1) reduction in vivo may be aided by intermediate superoxide radical formation or by strong blue light (Briiggemann et al, 1993). We know very little about the movement of iron in the phloem sap.…”
Section: Future Dlrectlonsmentioning
confidence: 99%